(untitled) (Eurasian Journal of Engineering and Technology, 2023)
This article presents the results of research carried out by researchers on increasing the resource of loader bucket works. Previous studies have not addressed the issue of welding the bucket teeth of loaders. The main purpose of the study is to develop the method of welding the teeth of the loader bucket, the results of the experiments conducted on the study of the hardness and corrosion resistance of the materials, the parameters of the welding and the composition of the materials of the welding